Migration Factors Impacting Instructors’ Intention to Utilize Digital Tools for Teaching Sustainable Development - Li Ming; Nuttapong Jotikasthira; Jiang Songyu (Migration Letters, 2023)
Higher education for sustainable development is an essential topic in the digital area. This study aims to identify the factors affecting the teachers’ intentions to use digital tools to teach sustainable development and construct a structural equation model for encouraging instructors to use digital tools to teach sustainable development, a critical yet under-investigated domain. The research employs a quantitative method, gathering data from 644 valid questionnaires obtained through purposive sampling and an online survey. The findings enrich the application of the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB), demonstrating their capacity to elucidate the Intention to use digital tools in sustainable development education. The results reveal that Perceived Behavioral Control (PBC) and Subjective Norms of digitalization (SNod) positively influence the Intention to use digital tools, while the Perceived usefulness of digitalization (Puod) and Digital Attitude toward teaching sustainable development (DA) act as positive intermediary variables. The study also confirms the existence of a mediating effect in the model. These findings provide valuable implications for teachers and school administrators in implementing digital tools for sustainable development education. Future research is recommended to expand on these findings, further facilitating the integration of digital tools in teaching sustainable development.